PENGEMBANGAN “VE-BOARD”: MEDIA SEDERHANA UNTUK PEMBELAJARAN FISIKA KELAS X SMA - Harjono Harjono (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2022)
Media was an effort to encourage the learning process to be more interesting and measurable. Lots of media were provided in the learning process, especially in physics subjects. One of them was using a vector board. This research was aimed to: 1) Developing physics learning media through vector boards for vector addition and decomposition, 2). Knowing the feasibility of the resulting media, and 3). Knowing the effectiveness of the media. The method used was the ADDIE model (Analysis, Design, Development, Evaluation). This research was conducted at SMAN Cahaya Madani Banten Boarding School Pandeglang-Banten. The indicators of achievement in this research can be seen from the results of expert validation, the results of students’ responses as test users, and students' cognitive learning outcomes. The instrument used was a validation questionnaire instrument, student response questionnaire, and post test results. The results of validation were 92.19. It belonged to the very decent category. The validation results for student worksheets obtained 92.86 which was a very feasible category. The result of using the product was 75.75% which included in the feasible category. The results of the implementation in the classroom obtained a cognitive score with an average of 79 from the minimum completeness criteria limit (KKM) of 75, with the highest score was 100 and the lowest score was 54. In addition to student learning outcomes in the cognitive field, the results of student responses in using ve-board media were also obtained into 80.4% which included a very good category. This meant that students responded positively in learning activities using ve-board. In addition, 80% of students stated that making ve-board media was easy. From this research, it can be concluded that with this Vboard, vertol learning became more real, it was not just in the form of images.